Hubungan Pola Asuh Orang Tua Dalam Pemberian Makan Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Palasari Kabupaten Subang - Salma Zulfa; Fitri Handayani; Ade Nuraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
The youth was very closely linked to growth and development. A balanced nutritional intake is required to ensure that the baby grows well. While nutritional deficiencies in the first year of growth can lead to irreparable effects. Stunting has become one of many nutritional problems. Stunting is a growing childhood problem caused by recurrent infections and chronic malnutrition. The study aims to find out the relationship between parental care patterns in feeding and stunting incidents in balita (rangge 1-5 year). This research used cross sectional research designs with correlational quantitative research methods. The study used the observation sheet and parenting feeding styles questionnaire (PFSQ) using the accidental sampling approach with a total sample of 62 parents who have case in the Puskesmas Work Territory of Palasari Subang District. This study used data analysis of the Chi Square correlation test. The results of the study showed that the majority gave democratic parental care, 25 (40.3 %) and most did not experience 36 stunts (58.1 %). The analysis of the Chi Square correlation test obtained p value= 0,000 (p<0.05), which indicated that the pattern of parental care in feeding had something to do with the occurrence of stunts in young children. It can be concluded that parental care can decrease incidence of stuntingand recommeended to take the right action to increasehealth for balita (rangge 1-5 year)